A Five-year Follow-up of Quality of Life in Women with Breast Cancer in Anthroposophic and Conventional Care. Issue 4 (2006) - Carlsson, Marianne; Arman, Maria; Backman, Marie; Flatters, Ursula; Hatschek, Thomas; Hamrin, Elisabeth
Abstract : Complementary and alternative medicine is used by many cancer patients in most parts of the world, and its use is increasing. The aim of the present study was to examine, over 5 years, the perceived quality of life/life satisfaction in two samples of women with breast cancer who were treated with anthroposophic care or conventional medical treatment only. Data from admission, after 1 year and after 5 years are used for the comparisons. On admission to the study the women in anthroposophic care perceived their quality of life to be lower than that of the women in the conventional treatment group, especially for emotional, cognitive and social functioning and overall quality of life. Sixty women who actively chose treatment with anthroposophic medicine and 60 individually matched women treated with conventional medicine participated. Quality of life was measured by the EORTC QLQ-C30 and the Life Satisfaction Questionnaire. Twenty-six women within anthroposophic care and 31 women within conventional medicine survived the 5 years. Effect size (ES) estimation favored the anthroposophic group in seven of the subscales mostly measuring emotional functioning. The ES for four of the subscales favored the conventional treatment group, mostly concerning physical functioning. After 5 years there were improvements in overall quality of life and in emotional and social functioning compared to admission for the women in anthroposophic care. The improvements took place between admission and 1 year, but not further on. Only minor improvements were found in the matching group.